Chitosan as a Biomaterial: Influence of Degree of Deacetylation on Its Physiochemical, Material and Biological Properties - Foster, Leslie John Ray; Ho, Sonia; Hook, James; Basuki, Monica; Marçal, Helder (PloS one, 2015)
Chitosan is a biomaterial with a range of current and potential biomedical applications. Manipulation of chitosan degree of deacetylation (DDA) to achieve specific properties appears feasible, but studies investigating its influence on properties are often contradictory. With a view to the potential of chitosan in the regeneration of nerve tissue, the influence of DDA on the growth and health of olfactory ensheathing cells (OECs) was investigated. There was a linear increase in OEC proliferation as the DDA increased from 72 to 85%. This correlated with linear increases in average surface roughness (0.62 to 0.78 μm) and crystallinity (4.3 to 10.1%) of the chitosan films. Mitochondrial activity and membrane integrity of OECs was significantly different for OECs cultivated on chitosan with DDAs below 75%, while those on films with DDAs up to 85% were similar to cells in asynchronous growth. Apoptotic indices and cell cycle analysis also suggested that chitosan films with DDAs below 75% were cytocompatible but induced cellular stress, while OECs grown on films fabricated from chitosan with DDAs above 75% showed no significant differences compared to those in asynchronous growth. Tensile strength and elongation to break varied with DDA from 32.3 to 45.3 MPa and 3.6 to 7.1% respectively. DDA had no significant influence on abiotic and biotic degradation profiles of the chitosan films which showed approximately 8 and 20% weight loss respectively. Finally, perceived patterns in property changes are subject to change based on potential variations in DDA analysis. NMR examination of the chitosan samples here revealed significant differences depending upon which peaks were selected for integration; 6 to 13% in DDA values within individual samples. Furthermore, differences between DDA values determined here and those reported by the commercial suppliers were significant and this may also be a source of concern when selecting commercial chitosans for biomaterial research.